Background of Fost Children in The Raudhatul Yatama Orphanage, Kertak Hanyar District, Banjar District - Rosalini, Isabella; Abbas, Ersis Warmansyah; Jumriani, Jumriani; Triyono, Sigit; Sari, Raihanah (Journal of Social Development, 2024)
This study aims to: 1) Describe the background of foster children in the Raudhatul Yatama Orphanage, Kertak Hanyar District, Banjar Regency. 2) Describe the parenting style of foster children at the Raudhatul Yatama Orphanage, Kertak Hanyar District, Banjar Regency. 3) Describe the contribution of parental parenting to social studies education. This study uses a qualitative research method with a descriptive approach. The data collection techniques used are observation, interviews, and documentation. Data analysis uses data reduction, data presentation and conclusion drawn. Test the validity of the data using triangulation. The results of the study were that children living in the Raudhatul Yatama Orphanage, Kertak Hanyar District, Banjar Regency came from various diverse backgrounds, including orphans, orphans, underprivileged, and abandoned children. This orphanage accepts 30 children with various age ranges. Data collection is expected to help orphanages to understand the needs and obstacles faced by these children.  The orphanage management pays attention to children from these backgrounds. The orphanage is committed to providing the best care and education to all foster children, regardless of their family origin or background.